2020
DOI: 10.3389/fpubh.2020.579634
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress From Exposure to the Underground Space Environment

Abstract: There are a growing number of people entering underground spaces. However, underground spaces have unique environmental characteristics, and little is known about their effects on human health. It is crucial to elucidate the effects of the underground space environment on the health of humans and other organisms. This paper reviews the effects of hypoxia, toxic atmospheric particles, and low background radiation in the underground space environment on living organisms from the perspective of oxidative stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 85 publications
1
9
0
Order By: Relevance
“…As shown in Figure C, correlation analysis showed that dissolved Fe ( P < 0.05) and Ti ( P < 0.05) were positively correlated with the OP AA in three SLFs, suggesting that once entering SLFs, MNPs may release Fe/Ti ions or tiny corresponding metal-containing NPs, which may potentially enhance the formation of ROS in the respiratory system. Several studies have shown that transition metal ions entering the respiratory system can cause ROS by triggering chemical reactions, particularly Fenton and Fenton-like reactions of Fe ions. ,,, NPs, particularly those with particle sizes less than 20 nm, have a larger surface area/volume ratio and a high metal content, which exhibit a stronger ROS-inducing effect on primary bronchial epithelial cells. , In addition, PNCs of Fe- and Ti-containing NPs showed positive correlations with OP AA values in three SLFs, indicating that the rate of ROS generation of <1 μm fractions in three SLFs increased with the increase in PNCs of metal-containing NPs.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure C, correlation analysis showed that dissolved Fe ( P < 0.05) and Ti ( P < 0.05) were positively correlated with the OP AA in three SLFs, suggesting that once entering SLFs, MNPs may release Fe/Ti ions or tiny corresponding metal-containing NPs, which may potentially enhance the formation of ROS in the respiratory system. Several studies have shown that transition metal ions entering the respiratory system can cause ROS by triggering chemical reactions, particularly Fenton and Fenton-like reactions of Fe ions. ,,, NPs, particularly those with particle sizes less than 20 nm, have a larger surface area/volume ratio and a high metal content, which exhibit a stronger ROS-inducing effect on primary bronchial epithelial cells. , In addition, PNCs of Fe- and Ti-containing NPs showed positive correlations with OP AA values in three SLFs, indicating that the rate of ROS generation of <1 μm fractions in three SLFs increased with the increase in PNCs of metal-containing NPs.…”
Section: Resultsmentioning
confidence: 90%
“…17,18,20,64 NPs, particularly those with particle sizes less than 20 nm, have a larger surface area/ volume ratio and a high metal content, which exhibit a stronger ROS-inducing effect on primary bronchial epithelial cells. 65,66 In addition, PNCs of Fe-and Ti-containing NPs showed positive correlations with OP AA values in three SLFs, indicating that the rate of ROS generation of <1 μm fractions in three SLFs increased with the increase in PNCs of metal-containing NPs.…”
Section: Oxidative Potential Of <1 μMmentioning
confidence: 87%
“…It is interesting to note that we did not observe differentially expressed genes involved in hypoxia between the LB and NB experimental flies. Such genes were commonly registered during a biological response to industrial deep underground or cave conditions [ 74 ]. This fact can indicate a high quality of the ventilation system in DULB-4900.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that mammals in extreme environments exhibit obvious oxidative stress adaptations that manifest as changes in physiological features, oxidants, antioxidant enzyme activity, genetic damage, and even disease status ( Ramirez et al, 2007 ; Yu et al, 2020 ). For example, diving mammals ( Wilhelm Filho et al, 2002 ), hibernating bats ( Yin et al, 2016 ), and underground rodents ( Yu et al, 2020 ) exhibit enhanced glutathione and higher activity and expression of antioxidant enzymes, including superoxide dismutase, catalase, and glutathione reductase.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed that mammals in extreme environments exhibit obvious oxidative stress adaptations that manifest as changes in physiological features, oxidants, antioxidant enzyme activity, genetic damage, and even disease status ( Ramirez et al, 2007 ; Yu et al, 2020 ). For example, diving mammals ( Wilhelm Filho et al, 2002 ), hibernating bats ( Yin et al, 2016 ), and underground rodents ( Yu et al, 2020 ) exhibit enhanced glutathione and higher activity and expression of antioxidant enzymes, including superoxide dismutase, catalase, and glutathione reductase. Furthermore, genome-wide studies found that genes related to oxygen storage and delivery, and energy metabolism are subjected to strong and consistent selective forces in species under oxidative stress (including highland species, diving mammals, and flying bats) ( Nery et al, 2013 ; Qiu et al, 2012 ; Shen et al, 2010 ; Storz & Moriyama, 2008 ; Tian et al, 2016 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%